Deltora quest. Volume 3 - Niwano, Makoto, 1964-; Kobayashi, Mayumi; Rodda, Emily (New York : Kodansha Comics, 2011)
After finding the topaz, Jarred and friends set off to look for the next gem of the Belt of Deltora at the Lake of Tears, but they pass through the territory of Thaegan on their way there, a route the evil sorceress plans to make them regret.
"A Kodansha Comics trade paperback original"--T.p. verso.
"First published in Japan in 2006 by Kodansha, Ltd., Tokyo"--T.p. verso.
"T Ages 13+"--Cover p. [4].
Translated from the Japanese.
Translation of: Derutora kuesuto.
Adult.
Keywords: Rodda, Emily -- Adaptations; Rodda, Emily -- Adaptations; Friendship -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Inheritance and succession -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Orphans -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Fantasy graphic novels; Friendship -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Inheritance and succession -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Manga; Orphans -- Comic books, strips, etc -- Fiction; Fantasy comic books, strips, etc; Graphic novels